Teacher motivation and its impact on the quality of education especially in disadvantaged areas: Challenges and opportunities for education policy - Hornyák, Ágnes (Edelweiss Applied Science and Technology, 2025)
Teacher motivation is a crucial component of educational quality and sustainability. In the face of 21st-century global challenges—including teacher shortages, digitalization, and increasing student diversity—the professional role of teachers is undergoing significant transformation. This study explores teacher motivation within disadvantaged educational environments, focusing on its drivers, consequences, and the implications for educational policy. Based on qualitative interviews with 24 practicing teachers, analyzed using Atlas.ti7, findings show that motivation is shaped by both intrinsic factors—such as self-fulfillment, a passion for teaching, and student-centered commitment—and extrinsic factors, including salary, career progression, social recognition, and institutional support. A lack of motivation significantly impacts teaching effectiveness, increases burnout, and leads to higher attrition, particularly in early career stages. Teachers with low motivation are less likely to apply innovative methods, show less responsiveness to student needs, and often contribute to weaker learning outcomes—especially detrimental for disadvantaged students, as it amplifies educational inequality. Furthermore, low motivation reduces collaboration among teachers and limits the school’s adaptability to external changes. The study highlights the urgent need for policy interventions aimed at strengthening motivational resources, particularly in vulnerable educational contexts, to ensure equity, retention, and long-term resilience in education systems.